(3GdLOhi GdGbJUGOjI ddeTQhYGJ (B:s (3JMdjd h OQGSI (B/s - (3Hfj YWG, HSGe MSjfs ((3YeGf(B: s (3eQcR GdcJGH GdGcGOjej(B, s, 2010)
(3JYQja GdeTQhY h eQGMdg , JYQja JMdjd GdLOhi , VQhQI JMdjd h OQGSI LOhi GdeTQhY h CSdhH gPg GdOQGSI , h eQGMdgG GdeJeKdI aj eQMdI GdOQGSI eGbHd GdGSJKeGQ , eQMdI OQGSI GdLOhi GdJegjOjI h eQMdI GdOQGSI GdJaUjdjI dLOhi GdeTQhY , Jbjje LOhi GdeTQhYGJ h JMdjd GdQHMjI GdGLJeGYjI , CeKdI Ydi gjGcd h feGPL OQGSGJ GdLOhi eY OQGSGJ CShGb h eYGjjQ GdLOhi GdGbJUGOjI ddeTQhYGJ (B.s
(3eQGLY U(B.127s
Keywords: (3GdGbJUGOs; (3GdeTGQjYs